Desiring China : Experiments in Neoliberalism, Sexuality, and Public Culture - Rofel, Lisa, 1953- (Book collections on Project MUSE., 2007)
Through window displays, newspapers, gay bars, and other public culture venues, Chinese citizens are negotiating what it means to be cosmopolitan citizens of the world, individuals with needs, aspirations, and longings. Lisa Rofel argues that the creation of such 'desiring subjects' is at the core of China's contingent, piece-by-piece reconfiguration of its relationship to a post-socialist, neo-liberal-dominated world. In a study at once ethnographic, historical, and theoretical, she contends that neo-liberal subjectivities are created through the production of various desires - material, sexual, and affective - and that it is largely through their engagements with public culture that people in China are imagining and practicing appropriate desires for the post-Mao era. Drawing on her research over the past two decades among urban residents and rural migrants in Hangzhou and Beijing, Rofel analyzes the meanings that individuals attach to various public cultural phenomena and what their interpretations say about understandings of post-socialist China and their roles within it. She locates the first broad-based public debate about post-Mao social changes in the passionate dialogues about the popular 1991 television soap opera Yearnings. She describes how the emergence of gay identities and practices in China reveals connections to a trans-national network of lesbians and gay men at the same time that it brings urban/rural and class divisions to the fore. The 1999-2001 negotiations over China's entry into the World Trade Organization; a controversial women's museum; the ways that young single women portray their longings in relation to the privations they imagine their mothers experienced; adjudications of the limits of self-interest in court cases related to homoerotic desire, intellectual property, and consumer fraud - Rofel reveals all of these as sites where desiring subjects come into being.